Spatial Distribution of Education Facilities in Haveri District - Nagaraj, H; Karlawad, S. L. (National Geographical Journal of India, 2022)
Three countrywide programmes, District Primary Education Programme (DPEP); Surva Shiksha Abhiyan (SSA); and Rastriya Madyamic Shikshan Abhiyan (RMSA), have given great emphasis on reducing all kinds of disparities in access as well as participation in primary and secondary education at the district level. While secondary education is yet to be provided to all sections of population and to all the habitations, inequalities continue to persist in terms of provision of educational opportunities at all levels in the study area. The main objectives of the study are to examine the spatial distribution of primary and secondary educational facilities and to identify different levels of educational development based on the different variables at the taluka level. The present study has identified the levels of development on the basis of availability and population served by educational amenities in each taluk. Most of the taluks are found in the medium level of development and Ranebennur taluk (6.69%) is in the category of very high levels of development and Savanur taluk (3.52%) is i in the extremely low levels of development.